Development Challenges in Extremist Affected Areas Report of An Expert Group To Planning Commission - Planning Commission (Planning Commission, 2008)
The Planning Commission set up an Expert Group on "Development Issues to deal with the causes of Discontent, Unrest and Extremism" in May, 2006. It had 16 Members. The Terms of Reference included, inter alia, identification of processes and causes contributing to continued tensions and alienation in the areas of unrest and discontent, such as wide-spread displacement, forest issues, insecured tenancies and other forms of exploitation like usury, land alienation, etc.
Government of India
Government of India